Accuracy of cricothyroid membrane identification using ultrasound and palpation techniques in obese obstetric patients: an observational study. (November 2021) - Lavelle, A.; Drew, T.; Fennessy, P.; McCaul, C.; Shannon, J.
Highlights: Cricothyroid membrane (CTM) identification in obese obstetric patients may be difficult. Ultrasound (US) improves CTM midpoint identification when compared with palpation. CTM identification takes significantly longer to achieve with US than palpation. There is no correlation between perceived ease of landmark technique and accuracy. No correlation between perceived ease of landmark technique and time to identification. Abstract: Background: During performance of emergency front of neck access, the final step in management algorithms for the 'can't intubate, can't oxygenate' scenario, accurate identification of the cricothyroid membrane is crucial. Accurate identification using palpation techniques is low, with highest failure rates occurring in obese females. Methods: This prospective observational study recruited 28 obese obstetric patients. The cricothyroid membrane was identified using ultrasound, marked with an ultraviolet pen and covered with a dressing. The candidate was asked to perform cricothyroid membrane identification using landmark technique (group L) followed by ultrasound (group U). The primary outcome was the distance between the actual and estimated cricothyroid membrane midpoint. Secondary outcomes were the proportion of accurate assessments, time taken, and subjective ease of identification using a visual analogue score. Results: Distance from the cricothyroid membrane midpoint was shorter in group U than Group L (2.5 mm vs 5.5 mm, P =0.002). The proportion of correctly identified cricothyroid membranes was greater in group U than group L (71% vs 39%, P =0.015). Time required for identification was shorter in group L than group U (16.9 s vs 23.5 s, P =0.001). Visual analogue scores for ease of identification were lower in group U than group L (2.4 cm vs 4.2 cm, P =0.013). Conclusions: Ultrasound-guided cricothyroid membrane localisation was significantly more accurate but slower than the landmark technique in obese obstetric patients. As such, we recommend the use of pre-procedural identification of the cricothyroid membrane in this patient population and formal training of anaesthetists in airway ultrasound.